MENYINGKAP KEARIFAN ISLAM: MEMAHAMI HADIST TENTANG TEKNIK DAN METODE DAKWAH - Hafizah Aini Adisti (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The da’wah method is an indivdual’s attempt to influencer or invite someone or mad’u to carry Allah’s commands and avoid all his prohibitas. In essence the educational method taught by the prophet was the way prophet convenyet his message to his campanions, at a time when the prophet was not yet familiar with communication theories to convey the message of Alla’s message or shari’a, and what is dsscussed in this writing is the prophet’s method of preaching in educating students. Friends and people from the perspective pf hadist to from a theory in convenying da’wah, from the explanation above the author will discuss the meaning of da’wah methods, methods of da’wah at the time of the prophet Muhammad SAW, apart from that the author tries to look for hadist related to the tittle hadist about techniques and methods of da’wah. The method used in this research is a desctiptive qualitative method with a literature study approach that collects data and examines various types of documents that are useful for analysis.